2016
DOI: 10.1098/rspb.2016.0811
|View full text |Cite
|
Sign up to set email alerts
|

Elevated virulence of an emerging viral genotype as a driver of honeybee loss

Abstract: Emerging infectious diseases (EIDs) have contributed significantly to the current biodiversity crisis, leading to widespread epidemics and population loss. Owing to genetic variation in pathogen virulence, a complete understanding of species decline requires the accurate identification and characterization of EIDs. We explore this issue in the Western honeybee, where increasing mortality of populations in the Northern Hemisphere has caused major concern. Specifically, we investigate the importance of genetic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
257
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(269 citation statements)
references
References 74 publications
11
257
1
Order By: Relevance
“…In particular, DWV-infected bees started to forage at an earlier age and showed reduced lifespans and total activity spans than control bees. Finally, next-gen sequencing demonstrated that the DWV strain we used for inoculation belonged to the type B DWB master variant [52], which has recently been found to be an emergent, more virulent strain of the DWV virus [25] that currently appears to be the most common strain in Britain [25]. The fact that our DWV lysate was prepared from a randomly selected sample of bees with overt DWV infection symptoms suggest that this strain is now also common in Continental Europe.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, DWV-infected bees started to forage at an earlier age and showed reduced lifespans and total activity spans than control bees. Finally, next-gen sequencing demonstrated that the DWV strain we used for inoculation belonged to the type B DWB master variant [52], which has recently been found to be an emergent, more virulent strain of the DWV virus [25] that currently appears to be the most common strain in Britain [25]. The fact that our DWV lysate was prepared from a randomly selected sample of bees with overt DWV infection symptoms suggest that this strain is now also common in Continental Europe.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of DWV injected was estimated at 1.2 Â 10 4 -4.6 Â 10 5 DWV copies per bee, and was aimed at mimicking infection loads reported for bees with covert infections (1.4 Â 10 3 -2.4 Â 10 9 copies per bee, [51]). Based on Illumina ultrahigh throughput sequencing, the DWV strain used for inoculation was determined to belong to the type B DWV master variant [52], which has recently been found to be an emergent, slightly more virulent strain of the DWV virus [25] that is currently also the most common strain in Britain [25] (for details, see the electronic supplementary material).…”
Section: (C) Controlled Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The known DWV strains (Type A, B, and C), and recombinants thereof, may be linked to differences in DWV virulence in honey bee colonies (Martin et al, 2012;McMahon et al, 2016;Ryabov et al, 2014;Zioni et al, 2011), however, there is no evidence that strains may be specifically linked to wing deformities on bees, rather it appears that viral loads of DWV play a significant role in the expression of this phenotype in honey bees (Brettell et al, 2017). By comparison to the existing work on honey bees, our understanding about DWV transmissibility and its effect on the fitness of non-Apis bees, and other insects, is much more limited.…”
Section: Floral Resources Have Been Identified As a Potential Contactmentioning
confidence: 99%